Emperor penguin diorama installation - Field Museum of Natural History (1935)
Hand colored lantern slide showing two exhibit preparators, John Moyer and John LaBonte, installing penguin specimens in the Emperor Penguin diorama. The penguin on the far left is wrapped in newspaper.